2023
DOI: 10.1038/s41467-023-37976-x
|View full text |Cite
|
Sign up to set email alerts
|

Parabolic avalanche scaling in the synchronization of cortical cell assemblies

Abstract: Neurons in the cerebral cortex fire coincident action potentials during ongoing activity and in response to sensory inputs. These synchronized cell assemblies are fundamental to cortex function, yet basic dynamical aspects of their size and duration are largely unknown. Using 2-photon imaging of neurons in the superficial cortex of awake mice, we show that synchronized cell assemblies organize as scale-invariant avalanches that quadratically grow with duration. The quadratic avalanche scaling was only found fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…Such behavior, described by power laws, is called scale independence (or invariance; Goldenfeld, 1992 ). Power laws in critically self-organized systems extend past the size distribution of neural activity avalanches found from in vitro (Beggs and Plenz, 2003 ; Mazzoni et al, 2007 ; Pasquale et al, 2008 ) and in vivo (Petermann et al, 2009 ; Hahn et al, 2010 ; Capek et al, 2023 ; Salners et al, 2023 ) experiments. Such power laws include different macroscopically measurable quantities, such as the duration distribution of functional connections in EEG recordings (Lee et al, 2010 ), the duration of neural avalanches (Ehsani and Jost, 2023 ), and the power spectrum.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Such behavior, described by power laws, is called scale independence (or invariance; Goldenfeld, 1992 ). Power laws in critically self-organized systems extend past the size distribution of neural activity avalanches found from in vitro (Beggs and Plenz, 2003 ; Mazzoni et al, 2007 ; Pasquale et al, 2008 ) and in vivo (Petermann et al, 2009 ; Hahn et al, 2010 ; Capek et al, 2023 ; Salners et al, 2023 ) experiments. Such power laws include different macroscopically measurable quantities, such as the duration distribution of functional connections in EEG recordings (Lee et al, 2010 ), the duration of neural avalanches (Ehsani and Jost, 2023 ), and the power spectrum.…”
Section: Discussionmentioning
confidence: 57%
“…Such behavior, described by power laws, is called scale independence (or invariance; Goldenfeld, 1992). Power laws in critically self-organized systems extend past the size distribution of neural activity avalanches found from in vitro (Beggs and Plenz, 2003;Mazzoni et al, 2007;Pasquale et al, 2008) and in vivo (Petermann et al, 2009;Hahn et al, 2010;Capek et al, 2023;Salners et al, 2023) (Lee et al, 2010), the duration of neural avalanches (Ehsani and Jost, 2023), and the power spectrum. While most studies found that a power-law exponent of neural avalanche duration is around −1.5 (Beggs and Plenz, 2003;Millman et al, 2010;Cowan et al, 2013;Hesse and Gross, 2014), steeper exponents were induced by dopamine modulation (Stewart and Plenz, 2006), and by D1 receptor antagonists (Gireesh and Plenz, 2008).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A genuine challenge in comparing exponents estimated from different experiments with different recording modalities (spiking activity, calcium imaging, LFP, EEG, or MEG) arises from differences in spatial and temporal scale specific to a particular recording, as well as the myriad decisions made in avalanche analysis, such as defining thresholds or binning in time. Thus, one possible reason for differences in exponents across studies may derive from how the system is sub-sampled in space or coarse-grained in time, both of which systematically change exponents and ( Beggs and Plenz, 2003 ; Shew et al, 2015 ) and could account for differences in ( Capek et al, 2023 ). The model we presented here could be used as a test bed for examining how specific analysis choices affect exponents estimated from recordings.…”
Section: Discussionmentioning
confidence: 99%